TINJAUAN KETIDAKLENGKAPAN PENGISIAN RESUME MEDIS RAWAT INAP PASIEN JANTUNG DI RUMAH SAKIT PERMATA PAMULANG - SUCIPTO, SUCIPTO; PRATIWI, RITA DWI; Ammari, Rieko (EDU RMIK Jurnal Edukasi Rekam Medis Ilmu Kesehatan, 2022)
ABSTRACTBackground: Completeness of the medical resume is very important for information about the patient's identity, diagnosis and treatment received by the patient. Filling out an incomplete resume can lead to serious problems, especially when it comes to court. Completeness of the medical resume can be used to measure the quality of services provided by the hospital, measure the quality of medical records and for good documentation. Each patient who receives treatment must immediately be filled in on the medical resume. Medical resume filled out and signed by the officer providing care. In the medical resume, it must be recorded completely, the medical record officer checks the completeness of the medical resume regarding: Patient's name, date of birth, date of entry, Medical Record Number, Diagnosis, Action, DPJP Name and DPJP Signature. The purpose of this study was to determine the incompleteness of filling out the medical resume of cardiac polyclinic patients at Permata Pamulang Hospital. The research method used is descriptive. Collecting data using observation with checklists and interviews with interview guidelines. The population in this study used 53 medical record files of heart patients. The sample used is 53 samples with Total Sampling sampling technique. From the results of the study, it was found that the patient identity review was completely 100% complete, the most important review reports were 80.15% complete and some were incomplete at 19.75% and the author's authentication review was almost completely complete at 95.25% and 4.65. % almost nothing is incomplete. In addition, there are no Standart Operational Procedure related to filling out medical resumes and the lack of understanding from relevant officers about the importance of filling out medical resumes completely. Advice that can be given is should made standard operating procedures relating to charging resume. ABSTRAKLatar Belakang: Kelengkapan resume medis sangat penting untuk informasi tentang identitas pasien, diagnosis dan tindakan yang diterima oleh pasien. Pengisian resume yang tidak lengkap akan dapat mengakibatkan permasalahan yang serius terutama bila sampai ke pengadilan. Kelengkapan resume medis dapat digunakan untuk mengukur mutu pelayanan yang diberikan rumah sakit, mengukur mutu rekam medis dan untuk dokumentasi yang baik. Setiap pasien yang mendapatkan perawatan harus segera diisi di resume medis. Resume medis diisi dan ditandatangani oleh petugas yang memberi asuhan. Dalam resume medis harus dicatat dengan lengkap, petugas rekam medis memeriksa kelengkapan resume medis tentang: Nama pasien, Tanggal lahir, Tanggal masuk, Nomor Rekam Medis, Diagnosis, Tindakan, Nama DPJP dan Tanda Tangan DPJP. Tujuan Peneliti: dari penelitian ini adalah untuk mengetahui ketidaklengkapan pengisian resume medis pasien poliklinik jantung si Rumah Sakit Permata Pamulang. Metode penelitian yang digunakan adalah deskriptif. Pengumpulan data menggunakan observasi dengan lembar ceklis serta wawancara dengan pedoman wawancara. Populasi dalam penelitian ini menggunakan 53 berkas rekam medis pasien jantung. Sampel yang digunakan berjumlah 53 sampel dengan teknik sampling Total Sampling. Dari Hasil Penelitian: ditemukan pada review identitas pasien seluruhnya lengkap 100%, review laporang yang penting sebagian besar lengkap 80,15% dan sebagian kecil tidak lengkap sebesar 19,75% serta review autentifikasi penulis hampir seluruhnya lengkap sebesar 95,25% dan 4,65% hampir tidak ada yang tidak lengkap. Selain itu belum Kesimpulan: adanya SOP terkait pengisian resume medis dan kurangnya pemahaman dari petugas yang berkaitan tentang pentingnya mengisi resume medis dengan lengkap. Saran: yang dapat diberikan adalah sebaiknya dibuat SOP terkait dengan pengisian resume medis.